Ecological characterization of an ombrogenic peatland in magallanes: Towards a proposal of bioindicators for environmental monitoring Caracterización ecológica de una turbera ombrogénica en magallanes: Hacia una propuesta de bioindicadores de monitoreo ambiental - Monsalve, Erika; Muñoz Arriagada, Rene Santiago; Bahamonde, Nelson; Vidal Ojeda, Osvaldo Javier (My University, 2021)
Ombrogenic peat bogs are ecologically extreme ecosystems, where the restrictive conditions such as anoxia, high acidity and low availability of nutrients allow a gradual accumulation of the organic substrate known as peat. This substrate is of great commercial interest because it is exploited for horticultural purposes and energy biomass. The exploitation of peat, however, involves the removal of vegetation, which has an important effect on secondary succession and ecosystem resilience. The flora and vegetation of peat bogs in the Brunswick Peninsula (Magallanes), in an area susceptible to mining exploitation, was studied to characterize ecological indicators. Phytosociological surveys were carried out to determine attributes of composition and structure at the community and landscape scale. This information was collated with satellite images and analyzed by univariate procedures (e.g. KW, Pearson) and multivariate (e.g. NMDS, ISA, ANOSIM). The following types of ombrogenic peat bogs were differentiated: graminoid, chamaephytic, Sphagnum and pulvinated peat bogs, which were associated with a terrestrialization to paludification gradient, and decomposition. The highest average richness was recorded in the pulvinated peat bogs. The chamaephytic and graminoid bogs has the largest areas, while the pulvinated were distributed in a few hectares. Diagnostic species (e.g. Caltha appendiculata, Donatia fascicularis, Drosera uniflora, Myrteola nummularia) were associated with one or another type of vegetation, showing ecological preferences. No exotic species were recorded. This information can help define critical levels of resilience and propose management and restoration strategies in post-disturbance abandoned peatlands.
Keywords: biodiversity indicators; brunswick peninsula; pristine peats; sphagnum magellanicum; von post decomposition